Abstract Equilibria, Interactive Choice Sets and Walrasian Allocations - Roberto Serrano; Oscar Volij (Brown University, Department of Economics, 1998)
Consider an exchange economy with a finite number of agents, who are arbitragers, in that they try to upset allocations imagining plausible beneficial trades. Their thought process is interactive, in that agents are conscious that the others are also going through the same steps. With this introspective process, each agent constructs a supermarket, i.e., a set of bundles that he considers achievable, in the sense that a sequence of plausible trades with other agents yields those bundles. We shed additional light on a result of Dagan (1996), by showing that Walrasian allocations can be characterized also as those where each agent chooses optimally from his supermarket. In addition, we extend the analysis to economies without short sales, where the characterization of Walrasian allocations is also obtained. Our analysis provides a different behavioral assumption for Walrasian allocations and connects with the core convergence theorem.
Keywords: 330